2022
DOI: 10.3390/cells11121867
|View full text |Cite
|
Sign up to set email alerts
|

Role of Mitochondria Transfer in Infertility: A Commentary

Abstract: Mitochondria transfer techniques were first designed to prevent the transmission of diseases due to mutations in mtDNA, as these organelles are exclusively transmitted to the offspring by the oocyte. Despite this, given the crucial role of mitochondria in oocyte maturation, fertilization and subsequent embryo development, these approaches have been proposed as new potential strategies to overcome poor oocyte quality in infertile patients. This condition is a very common cause of infertility in patients of adva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…The autologous mitochondrial transplantation technology ( 178 ), focuses on increasing the number of healthy mitochondria in cells while avoiding the introduction of third-party DNA in gametes. It is reported that injection of mitochondrial from oogonial precursor cells(OPCs) while intracytoplasmic sperm injection (ICSI) can improve the quality of oocyte and pregnancy rate in the ICSI cycle of women with multiple IVF failure ( 70 , 71 ).…”
Section: Methods To Slow Down Ovarian Aging and Prolong Reproductive ...mentioning
confidence: 99%
“…The autologous mitochondrial transplantation technology ( 178 ), focuses on increasing the number of healthy mitochondria in cells while avoiding the introduction of third-party DNA in gametes. It is reported that injection of mitochondrial from oogonial precursor cells(OPCs) while intracytoplasmic sperm injection (ICSI) can improve the quality of oocyte and pregnancy rate in the ICSI cycle of women with multiple IVF failure ( 70 , 71 ).…”
Section: Methods To Slow Down Ovarian Aging and Prolong Reproductive ...mentioning
confidence: 99%
“…13 59 It has also been argued that mixing the nuclear and mitochondrial genomes from two oocytes might lead to deleterious interactions between one oocyte's nuclear DNA and the other oocyte's mtDNA, which is referred to as mitonuclear mismatch. 29 Female children would also pass mtDNA on to their offspring, so mismatch-based harm could affect future generations as well. 87 However, the validity of this concern has been questioned, considering that 'natural' reproduction also places mtDNA in a seminovel nuclear environment since the mitochondria inherited from the mother will previously not have been in contact with the father's nuclear DNA.…”
Section: Potential Harms Of Mrtsmentioning
confidence: 99%
“…However, early clinical trials have shown promising results. It was found how mitochondrial transfer in patients with idiopathic infertility showed that the technique was safe and well-tolerated and resulted in the birth of healthy infants [195]. Further research is needed to assess the long-term safety and efficacy of mitochondrial transfer in humans.…”
Section: Mitochondrial Transfer As a Tool For Tissue Engineering And ...mentioning
confidence: 99%